A double-edged sword: High interest rates in capital control regimes - Gudmundur S. Gudmundsson; Gylfi Zoega (Economics: The Open-Access, Open-Assessment E-Journal, 2016)
This paper describes the relationship between central bank interest rates and exchange rates under a capital control regime. Higher interest rates may strengthen the currency by inducing owners of local currency assets not to sell local currency offshore. There is also an effect that goes in the opposite direction: higher interest rates may increase the flow of interest income to foreigners through the current account, making the exchange rate fall. The historical financial crisis in Iceland provides excellent testing grounds for the analysis. Overall, the Icelandic experience does not suggest that cutting interest rates in small steps from a very high level is likely to make a currency depreciate significantly in a capital control regime, but it highlights the importance of effective enforcement of the controls.
Keywords: G01; E42; E52; E58; 330; financial crises; capital controls; policy rates; exchange rates